Employee Performance of Life Insurance Companies:The Mediating Effect of Organizational Citizenship Behavior - Suhardi Suhardi; Djoko Soelistya; Retno Purwani Setyaningrum; Nur Aisyah; Nora Pitri Nainggolan (Universitas Hayam Wuruk Perbanas, 2021)
This study aims to determine the impact of employee leadership and team member exchange through organizational citizenship behaviour on the employee performance of foreign life insurances. This research uses the purposive sampling method for selection. One hundred sixty respondents are participating in the research used to test the model studied. The data is collected using a questionnaire and then analyzed using the SEM AMOS program. This study showed that servant leadership positively affects organizational citizenship behavior, team member exchange, and employee performance. While team member exchange has a positive and significant impact on organizational citizenship behavior, team member exchange has a negative and significant effect on employee performance. Subsequently, organizational citizenship behavior positively and significantly impacts employee performance. The mediating effect indicated that team member exchange and servant leadership influence organizational citizenship behavior and affect employee performance. The study's results imply that when employees perform beyond their jobs (organizational citizenship behavior roles) and engage in team member exchange, they have quality social communication with the workgroup members. Additionally, employees who work under servant leadership can develop strong personal bonds. Employees with low levels of autonomy in their work can improve performance if mediated by organizational citizenship behavior.